2013
DOI: 10.1515/form.2011.108
|View full text |Cite
|
Sign up to set email alerts
|

A note on the existence of transition probability densities of Lévy processes

Abstract: We prove several necessary and sufficient conditions for the existence of (smooth) transition probability densities for Lévy processes and isotropic Lévy processes. Under some mild conditions on the characteristic exponent we calculate the asymptotic behaviour of the transition density as t → 0 and t → ∞ and show a ratio-limit theorem.MSC 2010: Primary: 60G51. Secondary: 60E10, 60F99, 60J35.Abstract. We prove several necessary and sufficient conditions for the existence of (smooth) transition probability densi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
109
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 101 publications
(111 citation statements)
references
References 23 publications
2
109
0
Order By: Relevance
“…A first version of this result was already proved in [32]. While (1.4) is an exact formula, we get (1.5) p t (0) ≍ λ B d ψ 0, 1/ √ t whenever the metric measure space R n , d ψ , λ has the volume doubling property.…”
Section: Introductionmentioning
confidence: 52%
See 2 more Smart Citations
“…A first version of this result was already proved in [32]. While (1.4) is an exact formula, we get (1.5) p t (0) ≍ λ B d ψ 0, 1/ √ t whenever the metric measure space R n , d ψ , λ has the volume doubling property.…”
Section: Introductionmentioning
confidence: 52%
“…In this case we have local volume doubling. Let us close this section with an observation from [32,Lemma 9] where it is shown that the volume doubling property for large radii entails that (1+ψ) −κ/2 ∈ L 2 (R n , λ) for some suitable exponent κ > 0. This, in turn, has implications for the smoothness of the transition densities, cf.…”
Section: Metric Measure Spaces and Negative Definite Functionsmentioning
confidence: 87%
See 1 more Smart Citation
“…Clearly, this property extends to all t ≥ t b by the Markov property of (X t ) t≥0 . For more details on the existence and properties of transition probability densities for Lévy processes we refer to [37] and references therein. Finally, we remark that in many cases of interest Assumption (A3) follows directly from (rough) space-time estimates of the densities p(t, x).…”
Section: Definition 21 (Symmetric Jump-paring Lévy Processes)mentioning
confidence: 99%
“…One of the key observations in [48] based on [50] was that the diagonal term of p t (x − y), i.e. p t (0), is then entirely controlled by the volume of the balls B d ψ .…”
Section: Introductionmentioning
confidence: 99%